Defining Sex-Specific Habitat Suitability for a Northern Gulf of Mexico Shark Assemblage - Drymon, J. M.; Dedman, S.; Froeschke, J. T.; Seubert, E. A.; Jefferson, A. E.; Kroetz, A. M.; Mareska, J. F.; Powers, S. P. (Frontiers in Marine Science, 2020)
Understanding the factors that influence species’ distributions is crucial for implementing effective management and conservation practices, yet difficult for highly vagile species like sharks. Many shark species demonstrate either spatial and/or temporal sexual segregation, further confounding accurate quantification of habitat suitability. Given the importance of understanding spatiotemporal patterns in the distribution of coastal shark assemblages, we sought to quantify sex-specific abiotic factors that influence seasonal variation in a coastal shark assemblage using data from a long-term fisheries-independent bottom longline program in the northern Gulf of Mexico. Catch data (individuals/100 hooks/hour) were coupled with a suite of potentially predictive variables: surface and bottom values for temperature (C) and salinity (psu), sea surface height (m), three-dimensional surface and bottom current velocity (u, v, w, in m/s), bottom dissolved oxygen (mg/l), depth (m), substrate grain size (mm), daylength (min), and distance from shore (km). Data were analyzed using boosted regression trees (BRT) to describe the relationships between catch data and environmental factors potentially influencing sex-specific species distribution and abundance. Between May 2006 and November 2018, we conducted 1,226 bottom longline sets and caught 13,742 individuals encompassing 67 species. The majority of the animals captured (74%) were elasmobranchs, primarily sharks. Two species from each of the following three categories were selected for further analyses: small coastal sharks (Atlantic sharpnose shark Rhizoprionodon terraenovae and blacknose shark Carcharhinus acronotus), large coastal sharks (blacktip shark C. limbatus and sandbar shark C. plumbeus), and shelf-associated sharks (smoothhound sharks, Mustelus spp. and scalloped hammerhead Sphyrna lewini). Depth and distance from shore were the strongest predictors of distribution and relative abundance, followed by longitude and bottom salinity; other factors (e.g. temperature, daylength, substrate grain size) were less predictive. For the six species examined, predictive factors were often the same for males and females, although the range of preferred values varied. Surprisingly, the importance of these predictors varied little across seasons. Collectively, our findings demonstrate that sexual segregation is the norm for sharks in the north-central Gulf of Mexico. Long-term fishery-independent monitoring to further quantify these sex-based differences in habitat use should be prioritized, particularly in light of impending climate change.